Layanan Diagnosa Deteksi Penyakit Jantung Dengan Forward Chaining Dan Fuzzy Logic Mamdani Berbasis Mobile - Ade Sutiari (J-INTECH ( Journal of Information and Technology), 2020)
Deaths caused by heart disease are very high based on research results. People often ignore the perceived symptoms. Currently existing services in the community is directly with a doctor or expert so it takes a long time and costs are not small to diagnose heart disease. One of the mobile devices Android is growing rapidly, with various features provided to make it easier for human work. With the Android smartphone so people can get information quickly and easily, including heart health information. This study aims to make an application of early detection of heart disease by doing the process of anamnesa. Knowing the symptoms and performing calculations using the Forward Chaining method as a first stage diagnostic useful to determine the type of heart disease and Fuzzy Logic Mamdani as a diagnosis of the second stage to determine the level of certainty of heart disease suffered. By utilizing Android smartphone then this application will be built in mobile in order to quickly and easily accessed.